Prevention of Preeclampsia - Sammya Bezerra Maia e Holanda Moura; Laudelino Marques Lopes; Padma Murthi; Fabricio da Silva Costa (Hindawi Limited, 2012)
Preeclampsia (PE) affects around 2-5% of pregnant women. It is a major cause of maternal and perinatal morbidity and mortality. In an attempt to prevent preeclampsia, many strategies based on antenatal care, change in lifestyle, nutritional supplementation, and drugs have been studied. The aim of this paper is to review recent evidence about primary and secondary prevention of preeclampsia.